The Association Between Length of Recovery Following Sport-Related Concussion and Generic and Specific Health-Related Quality of Life in Adolescent Athletes: A Prospective, Longitudinal Study. Issue 1 (January 2019) - Valovich McLeod, Tamara; Bay, R. Curtis; Lam, Kenneth C.; Snyder Valier, Alison R.
Abstract : Objective: Our purpose was to determine the association between concussion recovery and health-related quality of life (HRQOL). Setting: Secondary school athletic training facilities. Participants: Patients ( N = 122) with a concussion. Study Design: Prospective, longitudinal cohort. Main Measures: The Pediatric Quality-of-Life Inventory (PedsQL), PedsQL Multidimensional Fatigue Scale (MFS), and Headache Impact Test-6 (HIT-6) were completed at preseason and days 3 (D3), 10 (D10), and 30 (D30) postconcussion. The independent variable was the recovery group. Results: Interactions between group and time ( P < .001) were noted for all PedsQL subscales, except Social Functioning ( P = .75). Significantly lower scores were found among Prolonged than in Short on D3 ( P < .05). Significant interactions ( P < .001) were also noted for all MFS subscales. Pairwise comparisons for General and Sleep subscales revealed Prolonged had lower scores than Short and Moderate on D3 and D10. A group by time interaction was found for the HIT-6 ( P < .001), with scores being higher ( P < .01) in Prolonged than in Short on D3 and D10. Conclusions: Adolescents with a prolonged recovery demonstrated lower HRQOL in the immediate days postinjury, particularly in physical and school functioning, fatigue, and headache. There was a strong association between recovery length and school functioning. Additional research is needed to understand how to minimize the impact of concussion on HRQOL.